Interchangeability of Abstract and Concrete Arts of Postmodernism - Mona Haidar Ali Hassan (Peerian Journals Publishing, 2024)
This subject is a coherent unit for many metaphors resulting from rational features as simulations of rational things in nature, the person is a similar image to the realistic form, and other forms are abstract methods that have nothing to do with reality, but simulate pure intellectual concepts, this topic shows how to move in formal photography between formal vocabulary that varies from the abstract and the diagnosed in artistic experiments. The current research has been concerned with the study of (the exchange of the abstract and the personalized in the formation of postmodernism), it included four chapters, in the first chapter presents the problem of research, which centered on the study of the abstract and personalized formal context in the formation of postmodernism
Keywords: formation; centered; metaphors; abstract